Pelatihan Pembuatan Video Interaktif Math Game Bagi Guru- Guru Sekolah Dasar di Kecamatan Pakong - Yuliana Trisanti; Fairus Zabadi; Agus Subaidi (Yayasan Literasi Sains Indonesia, 2023)
Literacy numeracy skills are needed to solve everyday problems using mathematical knowledge or symbols and numbers. Literacy and numeracy require logical thinking so that it can make it easier for someone to understand mathematics, therefore by having numeracy skills, it is hoped that students can easily understand the material, analyze a problem, and solve problems. Numeracy literacy can be said to be knowledge in the skills to (1) determine various numbers and symbols related to solving practical problems, (2) analyze various information presented in the form of graphs, tables, diagrams or charts and then use the results of the interpretations listed to predict and determine a decision. From the results of observations in class V of SDN Pakong 1 and class IV of SDN Palalang, it shows that there is a lack of understanding and enthusiasm of students in the learning process so that the learning objectives have not been achieved. Based on the results of interviews with teachers at SDN Pakong 1 and SDN Palalang, it was found that teachers never used interactive video media in the learning process. So teachers need to make changes to improve learning media more creatively through the use of interactive math game video media to help achieve learning goals.